Diverse CO2-Induced Responses in Physiology and Gene Expression among Eukaryotic Phytoplankton - Hennon, Gwenn M. M.; Hernández Limón, María D.; Haley, Sheean T.; Juhl, Andrew R.; Dyhrman, Sonya T. (Frontiers in Microbiology, 2017)
With rising atmospheric CO2, phytoplankton face shifts in ocean chemistry including increased dissolved CO2 and acidification that will likely influence the relative competitive fitness of different phytoplankton taxa. Here we compared the physiological and gene expression responses of six species of phytoplankton including a diatom, a raphidophyte, two haptophytes, and two dinoflagellates to ambient (~400 ppm) and elevated (~800 ppm) CO2. Dinoflagellates had significantly slower growth rates and higher, yet variable, chlorophyll a per cell. The other phytoplankton tended to have increased growth rates and/or decreased chlorophyll a per cell. Carbon and nitrogen partitioning of cells shifted under elevated CO2 in some species, indicating potential changes in energy fluxes due to changes in carbon concentrating mechanisms (CCM) or photorespiration. Consistent with these phenotypic changes, gene set enrichment analyses revealed shifts in energy, carbon and nitrogen metabolic pathways, though with limited overlap between species in the genes and pathways involved. Similarly, gene expression responses across species revealed few conserved CO2-responsive genes within CCM and photorespiration categories, and a survey of available transcriptomes found high diversity in biophysical CCM and photorespiration expressed gene complements between and within the four phyla represented by these species. The few genes that displayed similar responses to CO2 across phyla were from understudied gene families, making them targets for further research to uncover the mechanisms of phytoplankton acclimation to elevated CO2. These results underscore that eukaryotic phytoplankton have diverse gene complements and gene expression responses to CO2 perturbations and highlight the value of cross-phyla comparisons for identifying gene families that respond to environmental change.